El Bateo y la administración Olaya Herrera (1930-1934) : de salvador de Colombia a un gobierno híbrido y timorato (2012)
ABSTRACT: Taking into account the satire’s subversive nature and its role in “social reproduction” of ideologies, this paper points at the position of the satirical journal El Bateo about Enrique Olaya Herrera’s government. It describes the gradual disappointment of this journal -attached to radical liberalism- about the “national concentration” government. It mentions how El Bateo supported Olaya’s candidacy through a “messiah-savior” image, and how it later subverted this very image by means of an open criticism to this government. For this analysis, some notes by George Balandier and Ernst Gombrich on the dramatic nature of power and on satire are collected.